Pemanfaatan Media Sosial Untuk Pelayanan Kesehatan: Analisis Bibliometrik - Ahmad Palemba; Achmad Nurmandi (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This study aims to analyze the role of social media in using public policy on health services in the literature Scopus indexed. Deep social media government has become more critical in e-government. Considering social media for taking the policy, the government is the internal medium to push public policy on services and health to increase the government's performance. This research analyzed 454 Scopus database documents from 2018-2023 using